The Impact of Fiscal Policy on Economic Growth in ASEAN-5 Countries - Hussin Abdullah; Chia Yien Lim; Muhammad Azam (International Journal of Supply Chain Management, 2019)
The issues of fiscal policy dependency, vulnerabilities of domestic economy, frail financial uphold, and small fiscal multiplier motivated this study to examine the relationship between fiscal policy and economic growth in ASEAN-5 for the period of 1970–2016. Based on the nature of the data, the Autoregressive Distributed Lag (ARDL) approach has used. The results reveals that fiscal policy instrument namely government expenditure is statistically significant in ASEAN-5 economies except for Indonesia. Results also shows that implementation of non-tax in the long run results in expenditure being significant in ASEAN-5 except in Indonesia; tax and non-tax are significant in the Philippines, Thailand, and Singapore; and debt is significant in Indonesia and Thailand. The policy contributes to the Philippines and Thailand to increase the rate of non-tax in support of the growing expenditure. Results in case of Singapore highly recommends increasing the rate of tax and non-tax to decline its accrued debt. Government authorities should be transparent to ensure growth stability through prudent and effective policy in aggregate demand using the fiscal instrument in ASEAN economies.